A Qualitative Analysis of the Coping Strategies of Substitute Teachers - Vorell, Matthew S. (Alberta Journal of Educational Research, 2012)
This study distinguishes whether substitute teachers enact coping strategies that mitigate the source of work-related stress (problem-centered) or coping strategies that enable them to adapt to stress created by work-related stressors (avoidance-centered). The author gathered data for this analysis by conducting 37 in-depth interviews with substitute teachers and shadowing 14 of them for a total of 122 hours of observation. Through a grounded theory analysis, a trend emerged that showed substitute teachers engaged in both problem-centered and avoidance-centered coping strategies, with a slight numerical advantage given to problem-centered strategies. By understanding how substitute teachers deal with these issues, scholars can prepare future generations of substitute teachers with successful coping strategies. Cette étude évalue dans quelle mesure les suppléants ont recours à des stratégies d’adaptation qui atténuent la source de stress professionnel (axées sur les problèmes) ou à des stratégies d’adaptation leur permettant de s’adapter au stress créé par des stresseurs liés au travail (axées sur l’évitement). L’auteur a collecté les données pour cette analyse en passant des entretiens en profondeur avec 37 suppléants et en observant 14 de ceux-ci pendant un total de 122 heures. Une analyse fondée sur une théorie à base empirique a révélé que les suppléants ont tendance à adopter tant des stratégies d’adaptation axées sur les problèmes que celles axées sur l’évitement, les premières affichant un léger avantage numérique. Si on comprend les mécanismes d’adaptation des suppléants, les formateurs peuvent fournir des stratégies d’adaptation valables aux générations de suppléants à venir.